Blades of freedom - Hale, Nathan, 1976- (New York : Amulet Books, 2020)
Presents, in graphic novel format, the story of the Haitian Revolution and its role in Napoleon's decision to sell Thomas Jefferson and James Monroe the whole Louisiana Territory, when they sought to buy only New Orleans.
Maps on endpapers.
A tale of Haiti, Napoleon, and the Louisiana Purchase.
Includes bibliographical references (page 127).
2.4
3-6
Keywords: Louisiana Purchase -- Comic books, strips, etc. -- Juvenile literature; Haiti -- History -- Revolution, 1791-1804 -- Comic books, strips, etc. -- Juvenile literature; Louisiana Purchase -- Cartoons and comics; Cartoons and comics; Nonfiction comics; Biographical comics; Comics (Graphic works); Graphic nonfiction; Louisiana Purchase -- Juvenile literature; Haiti -- History